The effect of control structures on the financial strategies of companies listed on the Johannesburg Stock Exchange - Uliana, Enrico,1950- (Stellenbosch : Stellenbosch University, 2012)
Dissertation (Ph. D.) -- University of Stellenbosch, 1991.